Pencapaian Sustainable Development Goals di Sumatera Barat melalui Pertanian Berkelanjutan - Dina Yulianti; Arry Bainus; Virtuous Setyaka; Deasy Silvya Sari; Alyandani Ayu Kinanti (Andalas Journal of International Studies (AJIS), 2024)
Sustainable Development Goals (SDGs) are a set of international agreements on efforts that must be made to create a just, prosperous, and safe world for humans and the planet Earth. Efforts to achieve SDG number 2, namely "zero hunger", need to be done by implementing sustainable agriculture. This article explains the implementation of sustainable agriculture in West Sumatra Province, which has prepared a "Regional Action Plan for Sustainable Development Goals." In the RAD, it is stated that the Provincial Government will build a sustainable food production system. This research was conducted using a qualitative method. Data collection was carried out through interviews with farmer groups and various government agencies, accompanied by a review of related documents. The researcher used a policy framework consisting of four factors proposed by Eyhorn et al. (2019) to realize sustainable agriculture. The results of this study indicate that the first factor, namely the transformation towards sustainable agriculture, is underway in West Sumatra Province. The second factor, namely cooperation with the market to absorb sustainable agricultural products, has been attempted; the other two factors, namely incentives and sanctions related to sustainable agriculture, still need to be implemented.